Individual Characteristic and Organizational Influence on Employee Performance at Rural Bank PT. Prisma Dana Main Branch Manado - Lumintang, Genita G; Tielung, Maria V. J.; Walangitan, Mc Donald B. (Archives of Business Research, 2024)
This study aims to examine the effect of individual characteristics variables and organizational characteristics variables on the performance of employees of PT. Prisma Dana Main Branch Manado. The stages of research methods in this study used quantitative research methods, where this is a scientific method to obtain valid data with the aim of discovering, proving and developing knowledge so that it can be used to understand, solve and anticipate problems in a particular field. In terms of type, this research is an explanatory research that explains the relationship between research variables, then determines the entire population of 32 which is used as a sample. The research design used is a type of survey research. The results showed that partially individual characteristics and organizational characteristics had a positive and significant effect on the performance of employees at PT. Prisma Dana Main Branch Manado and simultaneously, individual characteristics and organizational characteristics had a significant positive effect on the performance of employees of PT. Prisma Dana Main Branch Manado.